2021
DOI: 10.2147/cmar.s330473
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasound-Guided Acquisition of Portal Venous Circulating Tumor Cells as a Potential Diagnostic and Prognostic Tool for Pancreatic Cancer

Abstract: Background: Circulating tumor cells (CTCs) were a promising liquid biopsy for pancreatic cancer (PC) but circulate in low counts in peripheral blood. We evaluated the diagnostic and prognostic values of portal vein (PoV) CTCs in PC patients. Methods: PoV was aspirated under EUS guidance from 40 patients with suspected pancreaticobiliary cancers. Epithelial-mesenchymal-transition-related subtypes of CTCs were identified via immunofluorescence using EpCAM and Twist antibodies. The diagnostic and prognostic perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
(46 reference statements)
2
12
0
Order By: Relevance
“…Based on this finding, some studies compared portal and peripheral CTCs in patients with pancreatic cancer. Two recent studies of patients with advanced or metastatic pancreatic cancer showed a higher CTC detection rate in the portal vein than in the peripheral vein, and the number of CTCs derived from the portal vein, rather than CTCs from the peripheral vein, was associated with OS [ 11 , 12 ]. However, studies that included only patients with resectable pancreatic cancer showed inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on this finding, some studies compared portal and peripheral CTCs in patients with pancreatic cancer. Two recent studies of patients with advanced or metastatic pancreatic cancer showed a higher CTC detection rate in the portal vein than in the peripheral vein, and the number of CTCs derived from the portal vein, rather than CTCs from the peripheral vein, was associated with OS [ 11 , 12 ]. However, studies that included only patients with resectable pancreatic cancer showed inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…The portal CTC detection rate was greater than 80% in some studies, including our study, in which portal CTC was significantly correlated with survival. However, the portal CTC detection rate remained in the 60% range in studies that did not show such correlation [ 11 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeted genotyping ( GNAS / KRAS ) of cell-free DNA (cfDNA) from blood samples can also distinguish IPMN from control cases (sensitivity, 81%; specificity, 84.2%) and the amount of cfDNA detected is much higher in metastatic pancreatic ductal adenocarcinoma (PDAC) than in IPMN for differential diagnosis [ 51 ]. Considering the higher abundance of circulating tumor cells (CTCs) in portal vein blood compared to in peripheral blood, researchers have discovered that the count of mesenchymal-CTCs and vimentin+ CTCs correlates with a poorer differentiated tumor and a shorter survival [ 52 , 53 ].…”
Section: Genetic Signatures and Their Clinical Applicationmentioning
confidence: 99%